Settlement Problem Encroachment in Area Conservation Reserve Natural Mountains Cyclops Through Track Non-litigation - Deppa Ringgi; Rionaldi Riawan (International Journal of Social Sciences and Humanities, 2026)
Encroachment of conservation areas is a serious threat to the sustainability of the ecosystem, including in the Cyclops Mountains Nature Reserve, Jayapura, Papua Law enforcement through litigation is often ineffective and does not provide optimal results. This study aims to examine the resolution of encroachment conflicts in the Cycloop Mountains Nature Reserve through non-litigation channels. This study is a qualitative study, with normative legal methods and a descriptive analytical approach. The results of the analysis indicate that non-litigation resolution through mediation, negotiation, and empowerment of communities around the Cycloop Mountains Nature Reserve can be a more effective alternative in resolving encroachment problems. This approach is in line with the spirit of inclusive conservation area protection and recognition of the rights of indigenous peoples.